IOT Based Smart Garbage Alert System and Public Awareness Intimation Using Wireless Sensor Networks - Kayalvizhi, S; Mahendra Reddy, S; Mahidhar, M; Raja Reddy, G (International Journal of Engineering and Technology, 2018)
Squander administration is one of the essential issue that the world faces regardless of the case of created or creating nation. The key issue in the waste administration is that the trash receptacle at open spots gets flooded well ahead Of time previously the beginning Of the following cleaning process. It thus prompts different perils, for example, terrible smell and grotesqueness to that place which might be the main driver for spread of different sicknesses. To maintain a strategic distance from all suchdangerous situation and keep up open tidiness also, wellbeing this work is mounted on a brilliant waste framework. The primary subject Of the work is to build up a brilliant wise waste ready framework for a legitimate junk administration.